The Impact of Organizational Culture on Performance foundation of Kindergartens Managers in Lattakia governorate - Afield Study - Ali, Wafegah (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This Research aimed to Recognize the reality of the prevailing organizational culture on performance foundation of kindergartens managers in lattakia governorate, and recognize impact of organizational culture on performance foundation of kindergartens managers in lattakia governorate, also the impact of the variables ( the training courses, years of experience, the scientific qualification) in organizational culture, and Performance foundation. To achieve the object of the research a questionnaire has been included two dimensions to measures the Organizational Culture and Performance foundation then applied to a sample of (82) Kindergarten Managers for the academic year 2018/2019. And used the Descriptive analytical Method. Validity of the questionnaire was established though a jury of (7) of the teaching staff of educational at Damascus and Tishreen Universities. Pilot sample consisted of (26) Kindergartens Managers, Reliability was established by Cronbach – Alpha Reliability (0.972) for Organizational Culture dimensions, and (0.961) for Performance foundation to Kindergartens Managers. The research ended to the Degree of Organizational Culture Dimensions of Kindergartens Managers in Lattakia governorate was middle degree, and the Reality of the Prevailing Organizational Culture on Performance foundation of Kindergartens Managers in Lattakia governorate was middle degree. The Results have Shown a good Correlation connection Between Organizational Culture and Performance foundation for Kindergartens Managers, also there are found Impact of the variables (the training courses, years of experience, the scientific qualification) in Organizational Culture, and haven’t Shown the Impact of these variables in Performance foundation of Kindergartens Managers in Lattakia governorate.